Abundance and Diversity of Polychaete Worms in Kapuas Estuary, West Kalimantan - Junardi, Junardi; Riyandi, Riyandi (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
Estuaries provide valuable ecosystem services, but they are also subject to environmental pressures due to high anthropogenic activities. The diversity and abundance of Polychaete can be used as indicators of the health of the Kapuas estuary, but supporting data are currently lacking. The objective of this research is to assess the quality of the Kapuas estuary through a Polychaete community approach. The study employed a survey method by selecting ten Polychaete sampling points based on their surrounding environmental conditions. Samples were collected from each point using a Petite Ponar grab, filtered, sorted, and grouped by family. The Polychaete specimens were identified up to the genus level. The data were analyzed descriptively. A total of 108 Polychaete individuals were found, comprising nine genera and seven families. The highest abundance was observed in the genera Capitella (Capitellidae) and Sternaspis (Sternaspidae), with 778 ind.m-2and 667 ind.m-2, respectively. The diversity of Polychaete in the Kapuas estuary was classified as low, with diversity index ranging from 0.5 to 1.21. The high abundance, low diversity, and presence of indicator genera of organic pollutants such as Capitella indicate that the Kapuas estuary is affected by organic contamination